ADDITION OF SUPERIOR HETEROTROF BACTERIA MIXED IN FEED TO IMPROVE HEALTH OF SALINE TILAPIA Oreochromis niloticus - Simanjuntak, Lewi Maraditha; Lukistyowati, Iesje; Feliatra, Feli (Asian Journal of Aquatic Sciences, 2019)
This research was conducted in May 2019 until July 2019 which took place at the Laboratory of Marine Microbiology and the Laboratory of Fish Parasites and Diseases at the Faculty of Fisheries and Maritime Affairs, Riau University. The purpose of this study was to determine the effect of the addition of superior heterotrophic bacterial isolates that were sprayed on feed could affect the health of saline tilapia (Oreochromis niloticus) through erythrocyte and leukocyte blood images. The treatments are Kn, Kp, feed sprayed with B.cereus heterotrophic bacterial isolate solution (0.15% dose), feed sprayed with heterotrophic V. fluvialis bacterial isolate solution (0.15% dose), feed sprayed with combined Isolate solution. The results of the study of the addition of superior heterotrophic bacterial isolates sprayed on feed can improve the health of saline tilapia (Oreochromis niloticus) after 30 days of maintenance and post-infection of Aeromonas hydrophila bacteria showed that the treatment of P3 (combined isolates) which is the best treatment with a total leukocyte value of 89.67 x 103 cells / mm3, lymphocytes 80.33%, neutrophils 10.67%, monocytes 9.66%, total erythrocytes 235.00 x 104 cells / mm3, hematocrit 32.00% and hemoglobin 7.33 g / dL and weight growth absolute 7.05 g, a survival rate of 83.33%.